Professional Strategies of University Teachers: Neo-Weberian Ideas in the Realities of Russian Higher Education - A. V. Garmonova; E. A. Opfer; D. V. Shcheglova; S. V. Gavrilov (Высшее образование в России)
Based on the theoretical framework of Max Weber and the neo-Weberians, the authors consider the profession of a University teacher in the dichotomy of “work with filling” (value-rational strategies) and performing routine professional functions (goal-rational strategies). Based on the data of the study “Professional strategies of teachers of higher education in modern Russia” indicators (mobility level, employment rate, career paths) are selected and justified, which allow teachers to attribute their professional strategies to the goal-rational or value-rational.The study showed that most teachers adhere to a goal-rational strategy, limiting themselves to fulfilling the minimum requirements of a professional contract. Value-rational strategies are characteristic for teachers with a high level of competences. Most young teachers under 39 follow goal-rational strategy. Value-rational strategy is characteristic of pre-retirement teachers. This increases the risk of a decrease in the quality of higher education due to the ageing of teaching staff.The authors conclude that “social closure” of the teaching profession is legalized, while maintaining the status quo and agreeing with the rigid regulatory framework in the neo-Weberian tradition.